The effect of dark states on the intersystem crossing and thermally activated delayed fluorescence of naphthalimide-phenothiazine dyads - Cao, Liyuan; Liu, Xi; Zhang, Xue; Zhao, Jianzhang; Yu, Fabiao; Wan, Yan (Beilstein Journal of Organic Chemistry, 2023)
A series of 1,8-naphthalimide (NI)-phenothiazine (PTZ) electron donor–acceptor dyads were prepared to study the thermally activated delayed fluorescence (TADF) properties of the dyads, from a point of view of detection of the various transient species. The photophysical properties of the dyads were tuned by changing the electron-donating and the electron-withdrawing capability of the PTZ and NI moieties, respectively, by oxidation of the PTZ unit, or by using different aryl substituents attached to the NI unit. This tuning effect was manifested in the UV–vis absorption and fluorescence emission spectra, e.g., in the change of the charge transfer absorption bands. TADF was observed for the dyads containing the native PTZ unit, and the prompt and delayed fluorescence lifetimes changed with different aryl substituents on the imide part. In polar solvents, no TADF was observed. For the dyads with the PTZ unit oxidized, no TADF was observed as well. Femtosecond transient absorption spectra showed that the charge separation takes ca. 0.6 ps, and admixtures of locally excited (3LE) state and charge separated (1CS/3CS) states formed (in n-hexane). The subsequent charge recombination from the 1CS state takes ca. 7.92 ns. Upon oxidation of the PTZ unit, the beginning of charge separation is at 178 fs and formation of 3LE state takes 4.53 ns. Nanosecond transient absorption (ns-TA) spectra showed that both 3CS and 3LE states were observed for the dyads showing TADF, whereas only 3LE or 3CS states were observed for the systems lacking TADF. This is a rare but unambiguous experimental evidence that the spin–vibronic coupling of 3CS/3LE states is crucial for TADF. Without the mediating effect of the 3LE state, no TADF is resulted, even if the long-lived 3CS state is populated (lifetime τCS ≈ 140 ns). This experimental result confirms the 3CS → 1CS reverse intersystem crossing (rISC) is slow, without coupling with an approximate 3LE state. These studies are useful for an in-depth understanding of the photophysical mechanisms of the TADF emitters, as well as for molecular structure design of new electron donor–acceptor TADF emitters.
Keywords: charge-transfer; electron donor; intersystem crossing; TADF; triplet state